Early Diagnosis of AP5Z1/SPG48 Spastic Paraplegia: Case Report and Review of the Literature - Papoff, Francesca M. A.; Astrea, Guja; Mero, Serena; Chicca, Laura; Satolli, Sara; Pasquariello, Rosa; Battini, Roberta; Tessa, Alessandra; Santorelli, Filippo M. (Neuropediatrics, 2024)
Hereditary spastic paraplegias (HSPs) are a genetically heterogeneous group of neurodegenerative disorders clinically characterized by progressive lower limb spasticity with pyramidal weakness. Around a dozen potential molecular mechanisms are recognized. Childhood HSP is a significant diagnostic challenge in clinical practice. Mutations in AP5Z1, which are associated with spastic paraplegia type 48 (SPG48), are extremely rare and seldom described in children.We report the clinical, radiologic, and molecular studies performed in a child harboring novel biallelic mutations in AP5Z1.The child presented a neurodevelopmental disorder with slight lower limb pyramidal signs. Brain magnetic resonance imaging (MRI) showed minimal white matter changes in the frontal horns of the lateral ventricles and a normally shaped corpus callosum. Western blotting in cultured skin fibroblasts indicated reduced protein expression, which confirmed the genetic diagnosis and framed this as a case of protein reduction in a context of impaired autophagy.Our findings expand the spectrum of phenotypes associated with mutations in AP5Z1, highlighting their clinical and pathophysiologic overlap with lysosomal storage disorders. SPG48 should be considered in the differential diagnosis of neurodevelopmental disorders even when pyramidal signs are minimal and brain MRI not fully informative.
Keywords: HSP; AP5Z1; SPG48; neurodevelopmental disorders; lysosomal storage disorders